2006
DOI: 10.1079/asc200511
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of weight, fat and muscle depth in growing lambs using random regression models

Abstract: Genetic parameters were estimated using uni-and bi-variate random regression models for weight, eye-muscle depth and fat depth measures between 60 and 360 days of age. Each trait was measured up to five times in 50-day intervals following weaning on approximately 4000 Australian Poll Dorset Sheep. The model accounted for rearing type, dam age, management group and age of recording. The model used for analysing weight included quadratic, orthogonal polynomials for direct genetic and environmental effects, a lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Growth traits. Consistent with literature estimates, body weight traits were all moderately to strongly correlated (0.46 ± 0.04 to 0.89 ± 0.01; Table 5), with weights measured at closer ages having stronger phenotypic and genetic correlations than those measured at more distant ages (Fischer et al, 2006;Ingham et al, 2007;Huisman and Brown, 2008;Boareki, 2017). Positive genetic correlations between WWT, PWWT, and WTUS (0.82 ± 0.06 to 0.89 ± 0.01; Table 5) were favorable, as selection for these traits would be expected to increase production efficiency.…”
Section: Genetic Correlationssupporting
confidence: 84%
“…Growth traits. Consistent with literature estimates, body weight traits were all moderately to strongly correlated (0.46 ± 0.04 to 0.89 ± 0.01; Table 5), with weights measured at closer ages having stronger phenotypic and genetic correlations than those measured at more distant ages (Fischer et al, 2006;Ingham et al, 2007;Huisman and Brown, 2008;Boareki, 2017). Positive genetic correlations between WWT, PWWT, and WTUS (0.82 ± 0.06 to 0.89 ± 0.01; Table 5) were favorable, as selection for these traits would be expected to increase production efficiency.…”
Section: Genetic Correlationssupporting
confidence: 84%
“…Regarded to genetic correlations in this study, the results confirm what has been observed by other authors (Fischer et al, 2004(Fischer et al, , 2006Lambe et al;Sarmento et al, in press), that genetic correlations among weights at subsequent ages, close together, are high, tending to unity and the weights at younger ages are not under the same genetic control than those taken in later life.…”
Section: Resultssupporting
confidence: 80%
“…52-0 . 77 for TBLM (Nguyen et al, 1998 ;Hanisch et al, 2004;Hsu et al, 2005;Fischer & Van der Werf, 2006). Interestingly, TBFM and TBLM are highly correlated, phenotypically and genetically (Gray & Bauer, 1991 ;Zhao et al, 2006), suggesting that they may share common genetic factors.…”
Section: Introductionmentioning
confidence: 97%